Quality Control of Pharmacopuncture: A Comparative Study of Good Manufacturing Practice and External Herbal Dispensary Standards - Ji-Eun Han; Minjung Park; Tteul-; Jong-Hyun Park; Danny Oh; Kyeong Han Kim; Soo-Hyun Sung (Korean Pharmacopuncture Institute, 2021)
Objectives: We aimed to compare the external herbal dispensary (EHD) evaluation criteria for pharmacopuncture and the Korea Good Manufacturing Practice (KGMP) sterile medicine standards to contribute to the establishment of quality control criteria for pharmacopuncture.Methods : : We obtained the KGMP standards from the Ministry of Food and Drug Safety and the pharmacopuncture certification criteria from the Ministry of Health and Welfare of South Korea. The EHD evaluation items were classified into three categories: facilities, quality control, and validation. The evaluation items were compared with the KGMP sterile medicine criteria to determine their conformance with each other, followed by a discussion among the committee of six experts and their consensus to suggest the items to complement the EHD evaluation criteria.Results : : Among the KGMP sterile medicine criteria, 44 were related to the management of the facilities, and 32 pharmacopuncture evaluation items corresponded to these KGMP items (66.7%). Fifty-eight KGMP criteria were related to quality management, and 42 pharmacopuncture evaluation items corresponded to these KGMP items (72.4%). Twenty-five KGMP sterile medicine criteria were related to validation, and 11 pharmacopuncture evaluation items corresponded to these KGMP items (44.0%). Sixteen items under the pharmacopuncture EHD criteria corresponded to the KGMP sterile medicine criteria based on the consent of the experts. Among these, 4 were related to facility management, 6 were related to quality control, and 6 were related to validation.Conclusion : : For the safety and quality control of pharmacopuncture, there is a need to select the criteria for the mandatory items among the proposed pharmacopuncture-EHD criteria laws and systems to ensure that the pharmacopuncture materials are produced under the pharmacopuncture-EHD in compliance with the relevant requirements. More studies are needed to secure the safety level of pharmacopuncture materials corresponding to that of conventional medicine.